The Effectiveness of EGRA (Exposure, Generalization, Reinforcement, Application) Method in Teaching - Reski Pilu; Hardianto Hardianto; Ardhy Supraba (Jurnal Studi Guru dan Pembelajaran, 2020)
The research aims at finding out the appropriate way to increase grammar ability in learning simple past tense of the eleventh year students of SMA Negeri 1 Larompong. The population of this research is the eleventh year students of SMA Negeri 1 Larompong consists of IPA which is distributed into 4 classes and IPS into 2 classes. So, total number of population is 244 students. The sample of this research is 30 students from 5 students of each class XI IPA and IPS to the eleventh year students of SMA Negeri 1 Larompong. In this research the researcher used pre experiment method. Based on the data analysis, the researcher can conclude that teaching structure simple past tense by applying EGRA method was effective to increase the students’ understanding. It was supported by the achievement of the ideal score in the pre test 53.00. In this case, the mean score in the post test 86.00. It means that, the students had a good understanding in learning structure simple past tense by used EGRA method. So, it could be concluded that the applied of EGRA method in teaching simple past tense is effective.